Murder Judgement Due to Mistake in Person on the Jurisprudence, Islamic Penal Law and Common Law - Milad Amiri; Ebrahim Yaghouti; Assadollah Masoudimaqam; Ahmad Ommi (مطالعات فقه و حقوق اسلامی)
According to the theory of transferred malice in common law, in cases of mistake in person, the criminal intent is transferred from the failed intended purpose to the finished unintended purpose and the committed crime, without regarding the predictive ability of the unwanted victim is intentional. In this way, the committed crime against the real victim is considered as the crime of the intended purpose and has the same sentence. Because, the intention is transferred from a definite purpose to an indefinite or accidental purpose as a face of malice; without the mental presupposition of universality. Therefore, the perpetrator is exposed to two intentional charges of starting to kill the intended person and intentional murder of the unintentional person with a primitive intent of killing man. But, according to prominent Shiite jurists and jurisprudential rule such as ((We intend not to do and we do not intend)), the murder sentence resulted from a mistake in person is unintentional. Also, the sentence of this type of murder in case of intent to kill a certain respectable person on the Islamic Penal Code of Iran approved in 1392, citing Articles 144, paragraph (a) of Article 290 and paragraph (c) of Article 292 and paragraph (c) of Article 291, except in the case of rule of the footnote of Article 292, it is considered as unintentional.   As a result, citing some jurists the theory of transferred malice or paragraph (d) of Article 290 of the Islamic Penal Code or even the title ((similar crime)) in the paragraphs of Article 290, with the motive of protecting human beings to make this type of murder intentional, is not acceptable.